THE PLACE OF MEDIATION IN THE SYSTEM OF SOCIAL SCIENCES - Savchenko Viktor; Neskorodieva Inna (Legal Bulletin, 2021)
In modern conditions, mediation has been increasingly becoming the subject of discussion to determine its place in the social sciences. In this regard, the need for an analysis of the social sciences, which are most closely related to mediation, will be updated. The aim of the article was to determine the structural components of the concept of "mediation" and to determine the place of mediation in the system of social sciences. The main problem in determining the place of mediation in the social sciences is the lack of a unified approach to this issue. Used the content analysis, the following components of the concept of "Mediation" have been identified: process, conflict, mediator, parties. It was found that mediation is an interdisciplinary science, which is at the junction of a number of social sciences: law, economics, sociology, and psychology. Based on the results of the study was made conclusions: today, mediation does not have its definite and fixed place in the system of social sciences. It has been established that at present mediation cannot be considered only within the framework of one science. The scientific results obtained in the study could serve as the basis for the development of the conceptual foundations of mediation and the disclosure of the practical potential of this process in conflict resolution.